ROS-Sensitive Nanoparticles Co-delivering Dexamethasone and CDMP-1 for the Treatment of Osteoarthritis Through Chondrogenic Differentiation Induction and Inflammation Inhibition - Wu, Xiaodong; Li, Pengpeng; Cheng, Jian; Xu, Qiang; Lu, Beiji; Han, Conghui; Huo, Weiling (Frontiers in Bioengineering and Biotechnology, 2021)
Objective: Osteoarthritis (OA) is a common subtype of arthritis. To date, treatment of OA focuses primarily on alleviating pain and improving joint function. The lack of a vascular system within synovial joints and the rapid removal of agents due to synovial exchange hinder continuous delivery of OA drugs. However, these obstacles are being addressed by promising nanoscale drugs. Methods: We synthesize and assemble a hydrogen peroxide [H2O2, belongs to the category of active oxygen species (ROS)]-sensitive nanomicelle, which is loaded with the anti-inflammation drug dexamethasone and chondrogenic differentiation factor cartilage-derivedmor-phogeneticprotein-1. The micelle can induce bone marrow mesenchymal stem cells to repair cartilage while inhibiting joint inflammation. Results: The prepared nanoparticles were of uniform size and displayed an obvious core-shell structure. Under H2O2 stimulation, the shell layer could be removed gradually. The drug-loaded micelle effectively inhibited proliferation of activated macrophages, induced macrophage apoptosis with an anti-inflammatory effect, and caused the BMSCs to differentiate into chondrocytes. Conclusion: This work provides an experimental and theoretical basis for further development of a drug-loaded micelle in the healing of osteoarthritis.